All‐Dielectric Fabry–Pérot Cavity Design for Spectrally Selective Mid‐Infrared Absorption. Issue 3 (18th December 2021) - Akin, Buket; Linford, Matthew R.; Ahmadivand, Arash; Altindal, Semsettin
Abstract : All‐dielectric metamaterials that exhibit broadband absorption of infrared (IR) radiation are promising platforms for the development of modern and applied nanophotonic technologies ranging from precise biosensing to high‐resolution imaging and high photon‐yield light detection. Herein, bulk meta‐absorbers comprising dielectric layers to provide broadband absorption of mid‐IR light are structured and studied. Through computational investigations and experimental assessments, the geometric parameters of the metastructure are judiciously selected and the peak of absorption is tuned to encompass the mid‐wave IR (MWIR) to long‐wave IR (LWIR) wavelengths, where absorbance of over ≈95% is achieved in the conducted analyses. These results are obtained using numerical optimization to achieve the highest absorption peak values. Thus, based on the mechanistic understanding of the conducted study, the reported percentage is the highest possible absorption efficiency obtained by the absorber metastructure. Importantly, the projected meta‐absorber is polarization insensitive and performs consistently over a wide range of incidence angles. The engineered multilayer architecture based on artificial media provides new possibilities for the broadband manipulation and control of the IR light. Abstract : All‐dielectric metamaterials with broadband absorption cross sections at infrared (IR) wavelengths provide promising architectures for the development of modern nanophotonic technologies. Through extensive computational investigations and experimental assessments, the authors find that judiciously devised polarization‐insensitive all‐dielectric multilayer metastructures exhibit an exquisite absorption cross section, which encompasses mid‐wave IR (MWIR) to long‐wave IR (LWIR) wavelengths.